CLINICAL APPLICATIONS OF HEART RATE VARIABILITY - Magrupov, T.M.; Isaev , Kh.A. (Educational Research in Universal Sciences, 2023)
Although HRV has been the subject of many clinical studies targeting a wide range of cardiac and non-cardiac diseases and clinical conditions, consensus on the practical application of HRV in medicine has been achieved in only two clinical scenarios. A decrease in HRV can be used as a predictor of risk after acute myocardial infarction and as an early sign of the development of diabetic neuropathy.